GENE-05. THE LOSS OF SUCCINATE DEHYDROGENASE B EXPRESSION IS FREQUENTLY IDENTIFIED IN HEMANGIOBLASTOMA OF THE CENTRAL NERVOUS SYSTEM. (11th November 2019) - Kim, Se-Hyuk; Hoon Roh, Tae; Yim, Hyunee; Roh, Jin; Beom Lee, Kyi; Jeong, Seon-Yong; Kim, Jang-Hee; Hyun Park, So
Abstract: Succinate dehydrogenase (SDH) is a mitochondrial enzyme that plays an important role in both the Krebs cycle and the electron transport chain. SDH inactivation is associated with tumorigenesis in certain types of tumor. SDH consists of subunits A, B, C and D (SDHA, SDHB, SDHC, and SDHD, respectively). Immunohistochemistry for SDHB is a reliable method for detecting the inactivation of SDH by mutations in SDHA, SDHB, SDHC, SDHD and SDH complex assembly factor 2 ( SDHAF2 ) genes with high sensitivity and specificity. SDHB immunohistochemistry has been used to examine the inactivation of SDH in various types of tumors. However, data on central nervous system (CNS) tumors are very limited. In the present study, we investigated the loss of SDHB immunoexpression in 90 cases of CNS tumors. Among the 90 cases of CNS tumors, only three cases of hemangioblastoma showed loss of SDHB immunoexpression. We further investigated SDHB immunoexpression in 35 cases of hemangioblastoma and found that 28 (80%) showed either negative or weak-diffuse pattern of SDHB immunoexpression, which suggests the inactivation of SDH. Our results suggest that SDH inactivation may represent an alternative pathway in the tumorigenesis of hemangioblastoma.